Penentuan Kadar Flavonoid Total dan Aktivitas Antioksidan Ekstrak Etanol Daun Bidara (Ziziphus spina-christi L.) - Haeria, Hermawati, Andi Tenri Ugi Dg. Pine (STIFA Makassar, 2016)
Research on determination of total flavonoid content and antioxidant activity of ethanol extract of bidara leaves (Ziziphus spina-christi L.) has been conducted. This study aimed to determine the total flavonoid content and antioxidant activity of ethanol extract of bidara leaves (Ziziphus spina-christi L.) by using a UV-Vis spectrophotometer. Total flavonoid content was determined at a wavelength of visible light 437.55 nm using a comparison of quercetin. Antioxidant activity was performed by measuring DPPH (1,1-diphenyl-2-picrylhydrazyl) free radical scavenging by UV-Vis spectrophotometer at a wavelength of 516.94 nm. Free radical scavenging activities carried out by comparison with Troloks® radical. This study showed that total flavonoid content of ethanol extracts of bidara leaves (Ziziphus spina-christi L.) is equal to 1.5312%, and IC50 90.9584 ppm. This result indicates that the ethanol extract of bidara leaves (Ziziphus spina-christi L.) has potential as a powerful antioxidant.